Inovasi Pembelajaran Mufradat dengan Video dan Subtitle Bahasa Arab di PP. Hasan Munjahid Grobogan - Umam, Rochimul; Setiyawan, Agung (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
This research demonstrates the implementation of innovative learning through the utilization of Arabic-language videos and subtitles adopted by Pondok Pesantren Hasan Munjahid Grobogan. The study aims to provide insights into how the combination of videos and subtitles enriches students' learning experiences, particularly in mufradat learning. A qualitative approach was employed, utilizing classroom action observation, interviews, and documentation for data collection. The gathered data will be qualitatively analyzed. Results indicate that the innovative use of Arabic-language videos and subtitles in Pondok Pesantren Hasan Munjahid effectively facilitates mufradat understanding and alleviates students' boredom. Positive responses are reflected in increased interest and motivation, impacting task performance during video sessions. While the approach has merits, identified shortcomings include some students struggling to grasp content. Therefore, recommendations include Arabic reading and writing training, additional materials provision, and individual guidance to optimize learning outcomes.